2022
DOI: 10.3390/su14137895
|View full text |Cite
|
Sign up to set email alerts
|

Red Junglefowl Resource Management Guide: Bioresource Reintroduction for Sustainable Food Security in Thailand

Abstract: The domestication of wild animals represents a major milestone for human civilization. Chicken is the largest domesticated livestock species and used for both eggs and meat. Chicken originate from the red junglefowl (Gallus gallus). Its adaptability to diverse environments and ease of selective breeding provides a unique genetic resource to address the challenges of food security in a world impacted by climatic change and human population growth. Habitat loss has caused population declines of red junglefowl in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(45 citation statements)
references
References 76 publications
0
45
0
Order By: Relevance
“…To ensure the success of reintroduction programs, we must first address the complex hybrid issue. Cluster analysis using STRUCTURE can now determine the degree of hybridization and gene pool pattern by aggregating individuals into a single cluster relative to additional highly differentiated populations/species [ 11 , 59 , 60 ]. Our previous study indicated that three individuals (CPO09, CSI05, and CSI06) may have been the result of interspecific hybridization between Siamese and saltwater crocodiles [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the success of reintroduction programs, we must first address the complex hybrid issue. Cluster analysis using STRUCTURE can now determine the degree of hybridization and gene pool pattern by aggregating individuals into a single cluster relative to additional highly differentiated populations/species [ 11 , 59 , 60 ]. Our previous study indicated that three individuals (CPO09, CSI05, and CSI06) may have been the result of interspecific hybridization between Siamese and saltwater crocodiles [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Mae Hong Son Province in Northern Thailand (97 Hong Son chicken might additionally have undergone a genetic selective s study aimed to analyze the gene pool of three populations of Mae Hong Son ing 28 microsatellite markers and mitochondrial (mt) D-loop sequences to inv genetic diversity. The findings were then compared to a broad gene pool librar under the "Siam Chicken Bioresource project" [15,16]. The maximum entrop (MaxEnt) [23] was used, based on spatial suitability analysis of Mae Hong Son precisely assess land suitability for chicken production.…”
Section: Analysis Of Study Area For Habitat Suitability Of Mae Hong S...mentioning
confidence: 99%
“…Partial fragments of the Mitochondrial D-loop (mt D-loop) sequence were amplified by PCR using the following primers: Gg_D-loop_1F (5 -AGGACTACGGCTTGAAAAGC-3 ) and Gg_D-loop_4R (5 -CGCAACGCAGGTGTAGTC-3 ) [15,16,35,36]. Mt D-loop PCR amplification was conducted, as previously described by Singchat et al [16]. The PCR reactions were performed under the following conditions: An initial denaturation was conducted at 94 • C for 4 min, followed by 40 cycles consisting of 30 s at 94 • C, 45 s at 58 • C, and 30 s at 72 • C. The reaction was completed with a final extension step at 72 • C for 10 min.…”
Section: Mitochondrial D-loop Sequencing and Data Analysismentioning
confidence: 99%
See 2 more Smart Citations